2008
DOI: 10.1093/cercor/bhn167
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Regulation of DNA Damage-Induced Apoptosis in Neurons of Cerebral Cortex

Abstract: Cerebral cortical neuron degeneration occurs in brain disorders manifesting throughout life, but the mechanisms are understood poorly. We used cultured embryonic mouse cortical neurons and an in vivo mouse model to study mechanisms of DNA damaged-induced apoptosis in immature and differentiated neurons. p53 drives apoptosis of immature and differentiated cortical neurons through its rapid and prominent activation stimulated by DNA strand breaks induced by topoisomerase-I and -II inhibition. Blocking p53-DNA tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 95 publications
(143 reference statements)
5
75
0
Order By: Relevance
“…This hypothesis was based on the evidence that SMN and some of its binding partners function in DNA repair (17,18) and that human SMA fibroblasts show increased sensitivity to the DNA topoisomerase-I inhibitor camptothecin (78), which induces DNA-SSBs and apoptosis (51). Moreover, our experiments demonstrating DNA damage accumulation in SMA mouse skeletal muscles very early in the disease suggested that muscle-specific DNA damage repair defects could be a pathological mechanism in SMA (14).…”
Section: Fayzullina Andmentioning
confidence: 82%
See 1 more Smart Citation
“…This hypothesis was based on the evidence that SMN and some of its binding partners function in DNA repair (17,18) and that human SMA fibroblasts show increased sensitivity to the DNA topoisomerase-I inhibitor camptothecin (78), which induces DNA-SSBs and apoptosis (51). Moreover, our experiments demonstrating DNA damage accumulation in SMA mouse skeletal muscles very early in the disease suggested that muscle-specific DNA damage repair defects could be a pathological mechanism in SMA (14).…”
Section: Fayzullina Andmentioning
confidence: 82%
“…Etoposide (Sigma, St Louis, MO, E1383) was dissolved at 10 mM in 1:1 medium:DMSO, and further diluted to 10 lM in myotube differentiation medium for exposure to differentiated myotubes. This dosage was shown to induce reliable DNA damage in cultured differentiated mouse neurons (51). For the control condition, 1:1 medium:DMSO was diluted in differentiation medium at an equivalent volume.…”
Section: Etoposide Treatment Of Myotubesmentioning
confidence: 99%
“…However, recent studies suggest that Bak acts upstream of Bax in promoting mitochondrial apoptosis (25,45), and that Bak plays the central role in apoptosis of differentiated neurons (24). Moreover, Bak may play an exclusive role in oxidative stress-mediated apoptosis in the brain (25), and also in mitochondrial fragmentation (45).…”
Section: Discussionmentioning
confidence: 99%
“…S3 A and B). To confirm that age-related cochlear cell death was apoptotic, we conducted TUNEL staining to measure nuclear DNA fragmentation, a key feature of apoptosis (16,24), in 5-and 15-month-old Bak Ϫ/Ϫ and WT mice. Consistent with the SG neuron and OH cell counts, aging resulted in increased levels of TUNEL-positive cells in the WT cochlea, whereas levels of TUNEL-positive cells in the Bak Ϫ/Ϫ cochlea did not increase with age (Fig.…”
Section: Bak Deficiency Reduces Apoptotic Cochlear Cell Death and Delmentioning
confidence: 99%
“…The signal transduction mechanisms in neurons that link DNA damage to apoptosis are not well characterized, and the sensors of DNA damage in neurons are largely unknown (Martin et al, 2009). However, some observations suggest that DDR in postmitotic neurons may have survival checkpoint that serves to eliminate neurons with excessive DNA damage.…”
Section: Cell Cycle and Neuronal Apoptosismentioning
confidence: 99%